2011
DOI: 10.2495/wrm110711
|View full text |Cite
|
Sign up to set email alerts
|

Livestock wastes: fish-wealth solution

Abstract: A review of the use of livestock wastes for sustainable fish wealth creation was done, using information from literature and field survey. Livestock wastes including animal manure and poultry by-products, which are a menace to the environment, are sources of wealth creation in fish farming. In Nigeria, about 932.5 metric tonnes of manure is produced annually from the well established livestock industries which keep expanding at the rate of 8% year-1. Nigeria is the largest importer of frozen fish in the world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 3 publications
(1 reference statement)
1
19
0
Order By: Relevance
“…Thailand, Indonesia, China, and Vietnam are primary producers of shrimp (Globefish ) and China is the major exporter of tilapia, providing 70% of total U.S. imports in 2009 (USDA/ERS ). Both shrimp and tilapia are frequently grown in Southeast Asian countries in small 1‐ to 2‐acre ponds, and are fed raw animal manure (such as poultry or swine feces) as their primary source of direct or indirect nutrients (Little and Edwards ; Adewumi and others ). Foodborne pathogens such as Salmonella are frequently associated with animal manure (Koonse and others ) and studies have revealed that 8.5% of imported raw crustaceans (of which more than 93% of the samples was raw shrimp) were contaminated with Salmonella compared with 3.9% of domestic raw crustaceans (Heinitz and others ).…”
Section: Implications Of Importing Foodsmentioning
confidence: 99%
“…Thailand, Indonesia, China, and Vietnam are primary producers of shrimp (Globefish ) and China is the major exporter of tilapia, providing 70% of total U.S. imports in 2009 (USDA/ERS ). Both shrimp and tilapia are frequently grown in Southeast Asian countries in small 1‐ to 2‐acre ponds, and are fed raw animal manure (such as poultry or swine feces) as their primary source of direct or indirect nutrients (Little and Edwards ; Adewumi and others ). Foodborne pathogens such as Salmonella are frequently associated with animal manure (Koonse and others ) and studies have revealed that 8.5% of imported raw crustaceans (of which more than 93% of the samples was raw shrimp) were contaminated with Salmonella compared with 3.9% of domestic raw crustaceans (Heinitz and others ).…”
Section: Implications Of Importing Foodsmentioning
confidence: 99%
“…Some problems however associated with rapid growth in poultry industry include the large scale accumulation of poultry wastes including manure and litter which may pose disposal and environmental problems unless environmentally and economically sustainable management technologies are evolved (Bolan et al, 2010). Adewumi et al (2011) also noted that large turnout of wastes from poultry encourages the growth of microbes, attracts houseflies, constitutes health hazard to man, animals and thus becomes a menace to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the exception of a few cases in the Vhembe district, the project was a failure for reasons ranging from physical limitations such as long cold winters to poor water quality. A major problem, associated especially with earthen fishponds, is the build-up of turbidity, which is exacerbated by the application of organic manure (Adewumi et al 2011). Moringa oleifera seeds have been used in earthen fishponds to improve water quality (Grabow et al 1985;Kavitha et al 2011).…”
mentioning
confidence: 99%